(untitled) (American Journal of Islam and Society, 2012)
Gender and Islam in Africa is a great contribution to the scholarship on African women. The contributors, all of whom come from different disciplines, seek to elevate the status of women by promoting gender equality, human rights, and democracy in androcentric African societies. They appeal for more women to participate in the reshaping and reforming of women’s roles; assert that women were part of Africa’s development; and maintain that male religious scholars who interpret Islamic religious texts in a way designed to relegate women to second-class status, as opposed to Islam, are the primary cause of women’s predicaments. This work is divided into three major sections: “Women Re/produce Knowledge,” “Re/constructing Women, Gender, and Sexuality,” and “Shari‘ah, Family Law, and Activism.” The contributors cite many examples of female scholars, among them Nana Asma’u and Malama Aishatu Dancandu, and their production of knowledge before and after colonialism.